2014
DOI: 10.1159/000365662
|View full text |Cite
|
Sign up to set email alerts
|

One- to Four-Year Follow-Up of Endobronchial Lung Volume Reduction in Alpha-1-Antitrypsin Deficiency Patients: A Case Series

Abstract: Background: Lung volume reduction surgery can improve lung function and working capacity in severe heterogeneous emphysema. Endobronchial lung volume reduction (ELVR) performed by one-way valves inserted via a flexible bronchoscope can result in a moderate but significant improvement in lung function and exercise tolerance, eliminating the surgical risks. Objectives: Most studies of this method have excluded patients with α1-antitrypsin (AAT) deficiency, but small series of cases with positive short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 26 publications
0
25
0
1
Order By: Relevance
“…The remaining 12 individuals were followed up for at least 1 year: FEV 1 increased by a mean of 54%, quality of life was much improved and 2 individuals were taken off oxygen therapy. There was no significant deterioration in lung function during the 4-year follow-up [72].…”
Section: (Iv) Symptomatic Therapy Transplantation Lung Volume Reducmentioning
confidence: 75%
“…The remaining 12 individuals were followed up for at least 1 year: FEV 1 increased by a mean of 54%, quality of life was much improved and 2 individuals were taken off oxygen therapy. There was no significant deterioration in lung function during the 4-year follow-up [72].…”
Section: (Iv) Symptomatic Therapy Transplantation Lung Volume Reducmentioning
confidence: 75%
“…While clinical evidence from RCTs, controlled trials and case series [13,14,15,16,17,18,19,20,21,22,23] demonstrates that by achieving lobar occlusion in the absence of CV, significant lung volume reduction can be obtained with associated significant clinical responses in severe emphysema patients, the efficacy/safety profile of the Zephyr® valve has not been reported in a large-scale observational study under conditions of daily clinical practice. We now report the study design and interim clinical results of the LIVE Study which was designed to gather safety and effectiveness data on EBV therapy in the real-world setting.…”
Section: Introductionmentioning
confidence: 99%
“…Small randomized series showed also some yield for the surgical intervention. [6,7] This procedure has been recently suggested by Trotter et al [8] in 552 randomized patients and the authors demonstrated that the choice of LVRS techniques did not affect the outcomes. Due to an extremely limited respiratory reserve, this is the safest technique which minimizes possible air leaks.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Unilateral resection can be planned for the treatment of hemodynamic instability in selected cases. [7] Herein, we report lung volume reduction in a case with hemodynamic instability early after coronary artery bypass graft (CABG) surgery. Our approach resulted in satisfactory surgical outcomes without any harmful complications in such a difficult case.…”
mentioning
confidence: 99%